2020
DOI: 10.1111/ecog.04753
|View full text |Cite
|
Sign up to set email alerts
|

Climate and geographic distance are more influential than rivers on the beta diversity of passerine birds in Amazonia

Abstract: Variation in the spatial structure of communities in terms of species composition (beta diversity) is affected by different ecological processes, such as environmental filtering and dispersal limitation. Large rivers are known as barriers for species dispersal (riverine hypothesis) in tropical regions. However, when organisms are not dispersal limited by geographic barriers, other factors, such as climatic conditions and geographic distance per se, may affect species distribution. In order to investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 47 publications
3
36
0
6
Order By: Relevance
“…Variance in species composition captured by the first PCoA axis-birds: 0.09; fishes (high disp): 0.19; fishes (low disp): 0.18; bats: 0.14; dominant ants (bait): 0.09; mobile-forager ants (pitfall): 0.08; cryptic ants (Winkler): 0.14; termites: 0.10; butterflies: 0.12; ferns ? lycophytes: 0.13; gingers: 0.13; palms: 0.26 Silva et al 2005a, b;Boubli et al 2015;Silva et al 2019;Maximiano et al 2020), climate and geographic distance (Dambros et al 2017;Fluck et al 2020). We found that soil conditions and geographic distance were important predictors for all taxonomic groups, but their relative importance varied among taxonomic groups, and bellow we discuss the congruence and discrepancies among biological groups in their response to these factors.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Variance in species composition captured by the first PCoA axis-birds: 0.09; fishes (high disp): 0.19; fishes (low disp): 0.18; bats: 0.14; dominant ants (bait): 0.09; mobile-forager ants (pitfall): 0.08; cryptic ants (Winkler): 0.14; termites: 0.10; butterflies: 0.12; ferns ? lycophytes: 0.13; gingers: 0.13; palms: 0.26 Silva et al 2005a, b;Boubli et al 2015;Silva et al 2019;Maximiano et al 2020), climate and geographic distance (Dambros et al 2017;Fluck et al 2020). We found that soil conditions and geographic distance were important predictors for all taxonomic groups, but their relative importance varied among taxonomic groups, and bellow we discuss the congruence and discrepancies among biological groups in their response to these factors.…”
Section: Discussionmentioning
confidence: 48%
“…Because the Amazon river is the largest and oldest river in the region (Hoorn et al 2010) and has been hypothesized to have stronger effects on species composition than other rivers (e.g. Fluck et al 2020), we expected differences between regions separated by the Amazon river to be stronger than between other regions. We present results from the Tukey test with this distinction (see ''Results'' section).…”
Section: Raw Data Analysismentioning
confidence: 99%
“…The effect of dispersal on spatial beta-diversity can be assessed through the analysis of the geographic distance between sites, while the effect of environment can be tested by evaluating measures of habitat and land use types (hereafter 'land use') and climate (Luck et al, 2013;Wieczynski et al, 2019;Fluck et al, 2020). However, due to the spatial structuring of environmental gradients (i.e., a distance decay in environmental conditions), it is difficult to partition the unique effects of each (Leibold and Chase, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Amazon region is the result of pervasive biogeographical processes, with large rivers acting as geographic barriers to some taxa (Ribas et al 2012, Dias‐Terceiro et al 2015, Naka and Brumfield 2018) and promoting enough isolation to affect community assembly (Fluck et al 2020). There is evidence that large Amazonian rivers can affect bird composition (Oliveira et al 2017) and haemosporidian diversification (Fecchio et al 2018b), however, some insects may not be constrained by riverine barriers due to their dispersion capability (Dambros et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the interfluves of the Amazon basin in the community composition of vertebrate taxa has been well studied (Wallace 1852, Cracraft 1985). However, identifying the different dimensions responsible for variation in community composition (β‐diversity) may uncover the effects of riverine barriers on this host–vector–parasite system, and also reveal previously unknown biological interactions within this system (Clark and Clegg 2017, Fluck et al 2020). In this sense, analyzing different dimensions of β‐diversity such as the incorporation of functional trait differences between communities (Villéger et al 2010) can provide information regarding differences in the evolutionary history between communities (Leprieur et al 2012).…”
Section: Introductionmentioning
confidence: 99%